Kindergarten development and fertility intention: an empirical study from China - Wang, Jingyi; Gao, Lifei; Wang, Guojun (Frontiers in Sociology, 2026)
IntroductionFaced with the inevitable trend of low fertility, how to build a more sustainable society that enables people to have the number of children they desire is becoming a global problem.MethodsBased on data from the China General Social Survey and China Education Statistics, we use Poisson regression, ordered logit regression, bootstrap analysis and other methods to explore the relationship between kindergarten development and fertility intention.ResultsThere is a positive correlation between developing kindergartens and fertility intention. The robustness tests prove the reliability of the research results. Developing kindergartens improves fertility intention by supporting career aspirations and increasing leisure accessibility. Women with a higher education level exhibit a stronger association with the development of kindergartens.DiscussionAlthough the empirical evidence is based on fertility intentions rather than realized fertility outcomes, the observed evidence may offer potential directions for optimizing demographic structures and fostering sustainable socioeconomic development. In the future, countries with low fertility should take measures to increase the supply of high-quality kindergartens and relieve childcare pressure to effectively solve the problem of low fertility.